Legal Counseling on Occupational Health and Safety (OSH) as an Effort to Protect Students in Practice - Khomaini; Ratna Sari Dewi; Syaipul Puad Tarigan; Asrat Nita Wati; Muhammad Nurohim; Aflahtul Daffa (International Journal Of Community Service, 2026)
Occupational Safety and Health (OSH) is an important aspect in creating a safe campus environment, but its implementation still needs to be improved in various academic activities. The main problem at STIKes Flora is the lack of student awareness in applying Occupational Safety and Health (OSH) procedures during practical activities, such as using personal protective equipment and complying with standard operating procedures (SOPs), which can create potential work hazards. To address this problem, it is necessary to conduct legal counseling activities on occupational safety and health through coordination with the campus and student affairs departments. The implementation methods include interactive lectures, group discussions, case study presentations, and Q&A sessions. The material covers the legal basis and concepts of occupational safety and health (OSH), the application of OSH in student practical activities, and handling workplace accidents and emergency response. The results of this PKM activity show that OSH counseling effectively increases the knowledge and awareness of STIKes Flora students regarding the importance of implementing work safety standards during practical activities in both laboratories and field practice.